Investigating Converter Options for Automotive Grade Permanent Magnet Sychronous Generators - Mese, Erkan; Yasa, Yusuf; Akca, Hakan; Aydeniz, Mustafa G.; Ayaz, Murat; Tezcan, Murat (IEEE, 2013)
In this paper, converter options for an automotive class permanent magnet synchronous generator (pMSG) are investigated. There are two options to rectify and regulate voltage from AC to DC. These are uncontrolled rectifier/dc-dc converter and controlled rectifier. Each converter topologies are explained and their comparison is performed. The comparison considers generator apparent power, efficiency, power flow ad cost. As far as converter effects on the generator apparent power rating and system efficiency are concerned, uncontrolled rectifier/dc-dc converter seems to be superior. On the other hand, controlled rectifier option has cost advantage over uncontrolled rectifier/dc-dc converter topology. A tradeoff exists between converter cost and PMSG utilization while making decision between two topologies.
Keywords: Permanent magnet synchronous generator; hybrid electric vehicle; uncontrolled rectifier; dc-dc converter; controled rectifier; Energy & Fuels; Engineering